Optimizing the capital structure of the company to maximize its profits by using neural networks on the example of building companies - Suler, P. (Математичне моделювання в економіці, 2016)
Nowadays, there are many methods meant for the optimization of an enterprise capital structure. Thus, the aim of this contribution is to find the most efficient way of a company´s possession capital structure. The article simply strives to find such a capital structure that ensures an adequate profit, respectively equity evaluation provided for money. For this purpose, balance sheets, respectively their parts informing about the sources of enterprise financing and the results, respectively only the total profit after taxation of all enterprises running their business between 2006 to 2015, will be used. To find the model neural networks will be used – specifically a multi-layer perceptron network and a neural network of a radial basic function. A neural network which will help a construction company find a suitable financing source structure so, that it could reach the requested ROE of 10%. The model will be useful not only for a building company management but also for evaluating its performance and health by the competitors, creditors or suppliers.